The impact of resident involvement and postgraduate year on head and neck surgery for obstructive sleep apnea - Mihai A. Bentan; Elizabeth Mastoloni; Lawrance Lee; Ryan Nord (PLoS ONE, 2025)
To assess the impact of resident involvement and resident postgraduate year (PGY) on head and neck obstructive sleep apnea (OSA) surgical outcomes. We analyzed head and neck OSA surgeries from 2005–2012 via the National Surgical Quality Improvement Program database. Demographic, preoperative, and postoperative variables were analyzed via multivariate regression to determine the impact of resident involvement and resident PGY on 30-day outcomes. Of 975 surgeries, 234 (24.0%) involved a resident: 120 (51.3%) involved a junior (PGY 1–3) resident and 114 (48.7%) involved a senior (PGY 4–5) resident. Multivariate analysis showed no significant impact on surgical, medical, or overall complication rates with resident involvement (all p > 0.05). Likewise, after separation of involved residents into junior or senior cohorts based on PGY, neither junior nor senior resident involvement significantly increased the odds of medical, surgical, or overall complications compared to operations performed by the attending alone (all p > 0.05). Resident involvement significantly increased readmission rates (6.1% versus 1.4%, p = 0.041) and operation time (92.1 ± 59.9 minutes versus 53.6 ± 42.0 minutes, p < 0.001) when compared to cases without resident involvement. Resident involvement in OSA surgery does not significantly impact rates of surgical medical, or overall complications. However, resident involvement increases 30-day readmission rates and almost doubles operation time, suggesting that resident involvement in head and neck OSA surgery remains relatively safe but further efforts to improve efficiency are likely needed.